Proposed Marketing Strategy to Increase Repurchase Intention of Brand.ABC - Anggit Kartika Sab'rina Sriyatna; Nita Garnida; Prawira Fajarindra Belgiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the extent to which Customer Satisfaction can affect Brand Loyalty. Customer Satisfaction can affect Repurchase Intention, and Brand Loyalty can affect Repurchase Intention at Brand ABC The sample of this research is 309 customer respondents who have purchased products at Brand ABC In this study, the authors used data collection methods through interviews and questionnaires. The data analysis technique in this study uses a validity test, reliability test and Structural Equation Modelling Partial Least Square (SEM-PLS) test. From the SEM-PLS test results obtained, BL = 0.981 CS + E1 and RI = -0.220 CS + 1.194 BL + E2., There is a strong and statistically significant positive influence between Customer Satisfaction and Brand Loyalty of Brand ABC customers. In addition, there is a strong and statistically significant negative influence between Customer Satisfaction and Repurchase Intention. Meanwhile, Brand Loyalty of Brand ABC customers has a positive and significant effect on their future Repurchase Intention.